Ergonomics of Work Performance and Work Productivity Aspects - Gempur Santoso (International Journal of Integrative Sciences, 2023)
Need to be analyzed and discussed about the appearance of the body at work or the ergonomics of balance and aspects of employee productivity. Because ergonomic appearance, namely the balance of the body at work and work tasks, will affect several aspects of work productivity. This writing method is carried out by means of a literature study, meaning that all data from several opinions are obtained from the literature. Then, some of the scientific opinion data is analyzed and discussed. The inference method uses a combination of several opinions and then concludes inductively